An Investigation of the Psychosocial and Demographic Determinants of Anxiety and Hopelessness During COVID-19 Pandemic - Erdogdu, Yesim; Kocoglu, Filiz; Sevim, Celil (Klinik Psikiyatri dergisi, 2020)
Objective: COVID-19, which has spread rapidly around the world since December 2019, has been defined as an infectious disease by the World Health Organization. Infection and mortality rates from COVID-19 are high and the COVID-19 pandemic has many negative impacts in health, economic and security fields. The aim of this study is therefore to examine the psychosocial and demographic determinants of anxiety and hopelessness during the COVID-19 pandemic among Turkish population. Method: The study group of the research consists of 1026 participants between the ages of 18 and 65 years. Personal Information Form, Beck Hopelessness Scale and Beck Anxiety Scale were used for data collection. Results: The majority of the participants reported that both national and global health, economic, and security precautions were not sufficient in fight against COVID-19 pandemic. About one in four participants had symptoms of moderate to severe anxiety and about one in three had symptoms of moderate to severe hopelessness. Women had significantly higher levels of anxiety compared to men. Participants who reported that the health, economics, and safety precautions were not adequate had higher levels of anxiety and hopelessness than those who reported that the precautions were adequate. Discussion: Given that the COVID-19 pandemic is associated with negative psychological and social consequences, the preventive programs for mental health should be promoted and the psychosocial support services should be made available to everyone in the society.
S, Celil/0000-0002-1723-006X; Delice, Yesim/0000-0003-2466-4605;
Keywords: COVID-19; SARS-CoV-2; Psychosocial Impacts; Anxiety; Hopelessness